PENDEKATAN HUKUM YANG MENIMBANG REHABILITASI DAN HUKUMAN BAGI PECANDU NARKOBA - Syahrul Hidayat, Syahrul; Ahmad Basuki Babussalam (Academos, 2025)
Drug addiction is a serious problem in many countries, with widespread negative impacts on individuals and society. Law enforcement against drug addicts involves both rehabilitation and punishment approaches, which creates complexities in handling these cases. The problem formulation in this article is (1) How effective is the rehabilitation approach compared to the punishment approach in dealing with drug addicts? (2) How can law be used to support efforts to prevent and treat drug addiction in society? This article aims to explore the role and importance of law enforcement in handling drug addict cases and to present an analysis of its effectiveness, efficiency, and compliance with legal principles and human rights in this context. This article uses a normative juridical method approach by analyzing in-depth the text of laws, regulations, and related court decisions. This analysis aims to understand the legal framework that regulates law enforcement against drug addicts and their right to rehabilitation. From the analysis conducted, this article concludes the importance of consistency in the application of the law against drug addicts to maintain justice, legal certainty, and the protection of human rights. In addition, this article also highlights the need for a balanced approach between rehabilitation and punishment in handling drug addict cases.